The Analysis of Work Ability On Employee Performance at PT. Smartfren Telecom Makassar: Analisis Kemampuan kerja terhadap Kinerja Karyawan Pada PT. Smartfren Telecom Makassar - Syam, Aswar Wijaya; Sudirman, Sudirman (Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to determine the job satisfaction of employees of PT Smartfren Telecom Makassar and aims to prove that there is a relationship between job satisfaction and employee performance of PT Smartfren Telecom Makassar.The type of research used is descriptive quantitative, in which the writer describes the results of observations and analyzes the data obtained in the field. To see the relationship between job satisfaction and employee performance at PT Smartfren Telecom Makassar, this research data was collected using the product moment correlation formula. After analyzing and discussing the problem, the authors conclude that employee performance at PT Smartfren Telecom Makassar is in the high category, namely 82%. This means that the employee's performance is in line with expectations, but there needs to be an increase to make it even better. Employee performance at PT Smartfren Telecom Makassar is in the high category, namely 82%. This means that the employee's performance is in line with expectations, but there needs to be an increase to make it even better. There is a significant relationship between job satisfaction and employee performance at PT Smartfren Telecom Makassar by calculating rcount = 0.317 > rtable 0.176 at the 95% confidence level. At the significance of the correlation there is a significant relationship between job satisfaction and employee performance, namely t count 3.67 > t table 2.617 at the 95% confidence level. Thus the hypothesis tested can be accepted